Psychological support via telemedicine for Brazilians affected by the war in Israel - Accorsi, Tarso; da Silva, Ana Lucia Martins; de Castro Filho, Josué; Morbeck, Renata Albaladejo; Pedrotti, Carlos Henrique Sartorato (LAJEC - Latin American Journal of Emergency Care, 2025)
.